2019
DOI: 10.3390/met9050482
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Difference in Mechanical Stability of Retained Austenite in Bainitic and Martensitic High-Carbon Bearing Steels using in situ Neutron Diffraction and Crystal Plasticity Modeling

Abstract: In situ neutron diffraction of the uniaxial tension test was used to study the effect of the surrounding matrix microstructure on the mechanical stability of retained austenite in highcarbon bearing steels. Comparing the samples with bainitic microstructures to those with martensitic ones it was found that the retained austenite in a bainitic matrix starts transforming into martensite at a lower strain compared to that within a martensitic matrix. On the other hand, the rate of transformation of the austenite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 40 publications
(66 reference statements)
2
16
0
Order By: Relevance
“…Equation (7) is the critical stress model that was originally developed by Haidemenopoulos et al [10]. Equation (7) has four fixed parameters (γ s , ρ, f , and E Str ) and six free parameters…”
Section: Derivation Of the Critical Stress Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Equation (7) is the critical stress model that was originally developed by Haidemenopoulos et al [10]. Equation (7) has four fixed parameters (γ s , ρ, f , and E Str ) and six free parameters…”
Section: Derivation Of the Critical Stress Modelmentioning
confidence: 99%
“…The modifications made to adapt Equation (7) for calculating the σ C of high-carbon quench-and-tempered steels are presented in this section.…”
Section: Modified Critical Stress Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic stress loads were simulated on 150 instantiations in ABAQUS using simple C3D8R elements using discretized representative volume element (RVE) methods [34,35]. Based on the microstructure observation in Section 2.1, 150 RVEs were generated to simulate the constitutive relationship at the weakest region.…”
Section: Crystal Plasticity Finite Element Modelmentioning
confidence: 99%
“…Dikic et al [8] found that as an effective nucleation matrix, V nitride particles could increase the nucleation rate of bainite in a medium-carbon steel. The amount and morphology of retained austenite are of great importance in the application of rolling bearings [9], especially in improving plasticity and toughness. Zhang's research group developed a process that can prepare nano-bainite on the surface and low-carbon martensite with good plasticity and toughness in the core of carburized bearing steel [10].…”
Section: Introductionmentioning
confidence: 99%